Kogo strzegły Lares Praestites? - Hartleb-Kropidło, Barbara (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
The paper discusses the Lares Praestites, whose role, customs, and festivities are described in Ovid’s Fasti 5, 129–139. The poet shows the Lares Praestites as archaic guardians of the City of Rome.